Analysis of Defense of Criminal Cases by Legal Aid Organizations (OBH) for the Poor as a Realization of Access to Justice - Hermawan; Andi Fajar Yulianto; Benedictus Indra Cristyanto (Universitas Muhammadiyah Palu, 2023)
Fulfillment of the right to legal aid for the poor is the establishment of rules that have legal consequences for Advocates or Legal Aid Organizations (OBH) to provide legal aid as a form of social and moral responsibility. Apart from that, to support the means and facilities for fair and equitable law enforcement, local governments are required to provide legal assistance so that the fulfillment of the right to legal aid for the poor is more guaranteed. Fulfillment of the right to legal aid to the poor in criminal cases is influenced by several factors, including Legal Aid Organizations (OBH), which are places of public defense. Advocates are parties who are directly involved in enforcing legal claims and professional obligations both in the field of litigation and non-litigation. The obligation to provide legal assistance is contained in the provisions of Article 22 paragraph (1) of Law Number 18 of 2003 concerning Advocates. In that article it is stated that Advocates are obliged to provide legal assistance free of charge to justice seekers who cannot afford it.